2021
DOI: 10.2147/ott.s316288
|View full text |Cite
|
Sign up to set email alerts
|

Study on Efficacy and Safety of Low-Dose Apatinib Combined with Camrelizumab and SOX Regimen as First-Line Treatment of Locally Advanced and Unresectable Gastric/Gastroesophageal Junction Cancer: A Protocol for an Open-Label, Dose Escalation and Extension Phase Ib Clinical Trial

Abstract: Background The standard treatment for advanced gastric/gastroesophageal junction cancer (AGC/GEJC) is palliative chemotherapy combined with targeted therapy. The SOX regimen (S-1 plus oxaliplatin) is recommended as neoadjuvant or palliative first-line chemotherapy in Asian patients. Apatinib, an oral VEGFR tyrosine kinase inhibitor, is associated with additional survival benefit as third- or subsequent-line therapy. However, the median overall survival time of AGC/GEJC is only 8–11 months in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After the duplicate literatures were eliminated, the titles and abstracts of the literatures were read. Based on the inclusion criteria and exclusion criteria, 20 literatures were finally included in this systematic analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The screening process is shown in Figure 1.…”
Section: Screening Process and Results Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…After the duplicate literatures were eliminated, the titles and abstracts of the literatures were read. Based on the inclusion criteria and exclusion criteria, 20 literatures were finally included in this systematic analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The screening process is shown in Figure 1.…”
Section: Screening Process and Results Of Literaturementioning
confidence: 99%
“…All the included 20 literatures [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] reported DCR, and the heterogeneity among 20 studies was low (P = 0:87, I 2 = 0%). The fixed effect model was used to analyze the data, which showed that the ROO of gastric cancer patients in the observation group was significantly higher than that in the blank group (OR = 3:09, 95% CI [2.29, 4.16], P < 0:01), as recorded in Figure 4 for details.…”
Section: Dcrmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, our team carried out a dose escalation and extension phase Ib clinical trial (SPACE) on the first-line treatment of potentially resectable and initially unresectable AGC/GEJC with low-dose apatinib combined with camrelizumab and the SOX regimen ( 20 ). At first, all patients received this combined regimen (3 weeks/cycle) for a maximum of eight cycles, followed by apatinib and camrelizumab as maintenance therapy until discontinuation for any reason.…”
Section: Discussionmentioning
confidence: 99%
“…Our team then carried out the SPACE study to assess the efficacy and safety of low-dose apatinib combined with camrelizumab and the SOX regimen as a first-line treatment of AGC/GEJC ( 20 ). The preliminary findings of four-drug combination showed an ORR of 94.7%, a disease control rate (DCR) of 100%, and a median PFS (mPFS) of 8.3 months.…”
Section: Introductionmentioning
confidence: 99%